Helical rim advancement – A technique to avoid keloid recurrence. (March 2019) - Kwek, James W.M.; Lee, T.S.; Loh, Ian C.Y.
Abstract: Introduction: Helical rim keloids occur commonly following ear piercings, trauma and previous surgeries and can be disfiguring. Many techniques have been developed to treated these disfiguring lesions with varying successes, however, individuals prone to developing keloids inadvertently recur despite best efforts. Objective: To determine whether helical rim advancement flap reconstruction following helical rim keloid excision can reduce recurrences. Design: Case series followed up to 2 years. Setting: Single Centre Tertiary Hospital Facial Plastics Service. Participants: All patients who consented to helical rim advancement reconstruction after keloid excision. Results: The authors report a series of 7 patients with helical rim keloids ranging from 1.2 cm to 5 cm in widest diameter treated with keloid excision and reconstruction with helical rim advancement flap technique. There were no recurrences within a mean of about 19 months post-operatively. Most patients report satisfaction with the cosmetic end-result. Discussion: From the authors' experience, helical rim advancement reconstruction following excision of keloids about 2.5 cm in widest diameter is an excellent tension-free option to avoid recurrence of helical rim keloids. Wound tension is a key risk factor for keloid formation. We hypothesise that the reason why there was no recurrence is because in helical rim advancement flap reconstruction, the underlying helical rim takes all the tension of closure off the dermis, resulting in tension-free skin closure. Conclusion: Helical rim advancement flap reconstruction is a viable technique to avoid recurrence and minimise cosmetic deformities of the pinna for selected helical rim keloids.